Choosing an expanded carrier screening panel: comparing two panels at a single fertility centre. Issue 2 (February 2019) - Bristow, Sara L.; Morris, Joshua M.; Peyser, Alexandra; Gamma, Amber; Singer, Tomer; Mullin, Christine; Onel, Kenan; Hershlag, Avner
Abstract: Research question: What are the factors contributing to similarities and differences in carrier rates between two expanded carrier screening (ECS) panels? Design: Retrospective cross-sectional study. A total of 7700 infertility patients who underwent ECS from one of two genetic testing laboratories (Panel A or Panel B) using a genotyping microarray were included in the study. Individuals presenting to the Centre between June 2013 and July 2015 underwent screening via Panel A. Those presenting between August 2015 and April 2017 underwent screening via Panel B. Self-reported ethnicity was recorded. Panel content, carrier rates for the overall study population and for comparable self-reported ethnicities, carrier couple rates, and the top 10 identified disorders were compared. Results: Of 4232 individuals screened by Panel A, 1243 were identified as carriers (29.4%). Panel B identified 1503 carriers among the 3468 (43.3%) participants ( P < 0.0001). Carrier couple rate also varied between panels (1.2% versus 3.1%; P  = 0.0017). A total of 311 disorders covering 2746 mutations were observed across the two ECS panels, with 372 (13.5%) shared mutations. Carrier rates did not differ for the shared mutations overall and across ethnicities. Significant differences were observed when comparing unique content in the overall population ( P < 2 .2 × 10 −16 ) and across ethnicities ( P < 2.2 × 10 −16 to 0.0010). Conclusions: Carrier rates in the overall population and across ethnicities vary widely based on panel content, and highlight the need to expand panel content as well as incorporate preconception carrier screening coupled with genetic counselling into routine assisted reproduction practice.